Neurodevelopmental–behavioural paediatrics. Issue 6 (December 2019) - McDowell, Michael; Lesslie, Jane
Abstract : Purpose of review: Neurodevelopmental–behavioural paediatrics (NBP) is a field of medical practice that has arisen in response to recent changes in child health epidemiology. This review considers how the profession of NBP is addressing clinical need, and discusses possibilities for future development of the field. Recent findings: Research publications relevant to NBP clinical practice focus primarily on cause (e.g. biology, imaging, neuropsychology), early detection, diagnostic methodologies and initial treatment strategies, with emphasis on psychotropic medication. Translation of this research implies that NBP clinical services should be undertaken using algorithmic methodologies, and evaluated against treatment attributable outcomes. These strategies and outcomes potentially define the central purpose of the profession; however, they may not be sufficient to best help the children seen. Summary: Two sets of information inform and extend consideration of NBP purpose and strategy. Firstly, longitudinal and adult studies indicate that even with treatment, problems persist in adult life for a significant proportion of children with neurodevelopmental–behavioural disorders. Secondly, NBP clinical practice deals with significant, irreducible complexity and uncertainty, arising from both child-diagnostic and contextual factors. Complexity limits the extent to which evidence-based clinical algorithms are able to inform care. Suggestions for how to address both challenges are offered.